Secure Localization and Time Synchronization for Wireless Sensor and Ad Hoc Networks - Poovendran, Radha; Roy, Sumit; Wang, Cliff; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
Secure Localization and Time Synchronization for Wireless Sensor and Ad Hoc Networks presents the latest research results in the area of secure localization and time synchronization for both wireless mobile ad hoc networks and wireless sensor networks. Recent advances in computing have exposed the potential security problems inherent in mobile ad hoc and wireless sensor networks. Subject to attacks and intrusions due to its open spectrum nature, wireless network localization and synchronization must be both robust and secure. Localization and time synchronization are critical processes for achieving sensor network security. Furthermore, issues such as energy constraints and mobility make the localization process even more challenging. This edited volume evolved from an ARO special workshop on Localization in Wireless Sensor Networks at the University of Washington, and includes contributions from the leading researchers in secure localization, time synchronization, and protocol verifications. This book presents the challenges posed, potential solutions, and directions for further research, while including implementation studies with mica2 mote sensors. Secure Localization and Time Synchronization for Wireless Sensor and Ad Hoc Networks is designed for researchers, developers and practitioners in the area of secure wireless systems. Advanced-level students in computer science, especially in the area of wireless systems and security, will undoubtedly find this an invaluable reference tool. This book is also suitable for use as a textbook for courses in wireless systems and security.
Localization Techniques -- Range-Free Localization -- A Beacon-Less Location Discovery Scheme for Wireless Sensor Networks -- Learning Sensor Location from Signal Strength and Connectivity -- Node Localization Using Mobile Robots in Delay-Tolerant Sensor Networks -- Experiences from the Empirical Evaluation of Two Physical Layers for Node Localization -- Secure Localization -- Robust Wireless Localization: Attacks and Defenses -- Secure and Resilient Localization in Wireless Sensor Networks -- Secure Localization for Wireless Sensor Networks using Range-Independent Methods -- TRaVarSeL-Transmission Range Variation based Secure Localization -- Secure Sequence-based Localization for Wireless Networks -- Securing Localization in Wireless Networks (using Verifiable Multilateration and Covert Base Stations) -- Distance Bounding Protocols: Authentication Logic Analysis and Collusion Attacks -- Location Privacy in Wireless LAN -- Secure Time Synchronization -- Time Synchronization Attacks in Sensor Networks -- Secure and Resilient Time Synchronization in Wireless Sensor Networks -- Securing Timing Synchronization in Sensor Networks.
Keywords: Engineering; Computer organization; Computer communication systems; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Electrical engineering; Engineering; Communications Engineering, Networks; Data Encryption; Data Structures, Cryptology and Information Theory; Computer Communication Networks; Computer Systems Organization and Communication Networks; Coding and Information Theory; Electronic books